Burnout pustakawan: Faktor-faktor dan dampak - Riya Fatmawati (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
This paper discusses the level of burnout in library staff, burnout is a term that describes the emotional state of a person who is tired and mentally, emotionally and physically saturated as a result of increasing job demands. The main source of burnout is due to the stress that develops continuously due to the long-term involvement of the provider and the recipient. Symptoms of burnout can be felt on physical, emotional, and behavioral symptoms. The burnout factors can come from marital status, gender, age, and work hours.